Sulfide Doped Cobalt Oxide Nanosphere as a Highly Efficient Electrocatalyst for Oxygen Evolution Reaction (Journal of Atomic and Molecular Sciences, 2019)
Electrochemical water splitting has been known as a promising and environmental approach toproduce hydrogen by avoiding relying on fossil fuels. Unfortunately, the efficient and large-scale $H_2$ production is still hindered by the sluggish kinetics of the oxygen evolution reaction (OER) at the anode sideof a water electrolyzer. Herein, we report a novel amorphous sulfide doped cobalt oxide (amorphous Co-S-O)nanosphere as an efficient electrocatalyst for OER. The Co-S-O electrode exhibits high HER activity and goodstability.
Keywords: OER; Electrocatalyst; Sulfide Cobalt; Nanosphere.